2019
DOI: 10.1111/jrh.12390
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs, and Attitudes About Contraception Among Rural Latino Adolescents and Young Adults

Abstract: PurposeLatino youth experience significant disparities in rates of teen pregnancy, and reproductive health needs of rural Latino youth are not well understood. The purpose of this study was to describe knowledge, beliefs, and attitudes about contraception among rural Latino adolescents and young adults (Latino youth).MethodsEighty‐four Latino youth, aged 15–24 years from rural Kansas communities participated in 15 focus groups (FG) and completed an individual survey. The survey assessed demographics and accult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Although CA PREP prioritizes services in low-income communities, this study did not assess other social determinants of health, including household socioeconomic status, insurance status, and geographic location, which other studies have shown to be associated with access to care as well as other adolescent health outcomes [ 17 , 47 ]. Because the study was based in California, which mandates sexual health education and confidential access to care for minors, these results may underestimate the access barriers that youth face in other states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CA PREP prioritizes services in low-income communities, this study did not assess other social determinants of health, including household socioeconomic status, insurance status, and geographic location, which other studies have shown to be associated with access to care as well as other adolescent health outcomes [ 17 , 47 ]. Because the study was based in California, which mandates sexual health education and confidential access to care for minors, these results may underestimate the access barriers that youth face in other states.…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of these different demographic characteristics may also amplify concerns among certain groups. For example, Latino youth living in rural areas often worry about privacy due to small and tight-knit communities and have limited services available [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Young-adult Hispanic women reported that adolescent pregnancy is normal and believe that birth control equates with abortion. 6 Mexican-American Hispanic women reported the reason they choose to undergo sterilization is difficulty in discussing contraception with their families and partners. 7 Hispanic women reported less conversations with their parents about how to say "no" to sex and about contraception use as compared to Black and White women.…”
Section: Introductionmentioning
confidence: 99%
“…The Hispanic ascribed gender roles of machismo and marianismo may influence the power balance of a relationship exposing the couple to high sexual risks. Machismo cites men as the decision makers 4 , 10 while marianismo portrays women as a follower to their partner in a sexual relationship. 11 To date, no studies can be found investigating the influence of ascribed Hispanic cultural gender roles including HIV knowledge, acculturation, attitudes, and sexual self-efficacy on protected sex in one single study.…”
mentioning
confidence: 99%